Competition through cooperation? The case of the German postal market - Toufic M. El Masri (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
How can small and medium-sized German postal providers ensure nationwide geographical coverage without the aid of the former monopolist? A closer look at the industry revealed that postal providers in Germany engage in different types of cooperation in order to expand their geographical coverage independently from the market leader. In order to shed light on the effects of cooperation, I conducted a theoretical analysis using a spatial economic model complemented by a brief game-theoretical discussion. Moreover, I provide the first descriptive and case study evidence from unique data collected in 2010 and 2011, within the framework of a German postal market survey. I found that small postal providers cooperate with each other in order to extend their geographical service area and to succeed in the market. Furthermore, I also found - in both the theoretical analysis as well as in the evidence - that there is a negative counter-effect stemming from this cooperation.
Keywords: D24; L22; L51; L97; 330; Cooperation; Competition; Germany; Network Industries; Postal Sector